BAURAN PEMASARAN DODOL SALAK â€œUD.MANDIRIâ€ DI DESA PANGU SATU KECAMATAN RATAHAN TIMUR KABUPATEN MINAHASA TENGGARA - Ayu Sagita Syah; Agnes E. Loho; Juliana R. Mandei (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objectve of this research is to know the marketing mix on â€œdodolsalak UD. Mandiri "Pangu Village, Ratahan Timur District, Southeast Minahasa Regency. This research was conducted from October to April 2019. The data used in this study are primary data and secondary data. The method of data collection is done by survey method. The sampling technique is done by using accidental sampling. The number of respondents is 20 people. Data collection use interview tehnique and the measuring instrument used is the Likert Scale. Data analysis was carried out descriptively. The results showed that the index numbers in the marketing mix strategyÂ  UD. Mandiri obtained for the average rating of respondents in the product aspect was 85.8%, the price aspect was 88%, the aspect of the place was 78.5% and the promotion aspect was 73% so that the overall rating of respondents was in the good category.Keywords: Marketing mix, dodol salak UD Mandiri, Skala Likert